2007
DOI: 10.1016/j.brainresbull.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic component odors emerge from mixtures after selective adaptation

Abstract: Humans cannot reliably identify the distinctive characteristic odors of components in mixtures containing more than three compounds. In the present study we demonstrate that selective adaptation can improve component identification. Characteristic component odors, lost in mixtures, were identifiable after presenting other mixture constituents for a few seconds. In mixtures of vanillin, isopropyl alcohol, l-menthol and phenethyl alcohol, this rapid selective adaptation unmasked each component. We suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 71 publications
4
56
1
Order By: Relevance
“…This accompanies the affirmation by Goyert et al (2007): olfactory receptors do not act as detectors of isolated molecular features, but more likely recognise entire molecules closely associated with perceived olfactory qualities.…”
Section: Polymentioning
confidence: 98%
“…This accompanies the affirmation by Goyert et al (2007): olfactory receptors do not act as detectors of isolated molecular features, but more likely recognise entire molecules closely associated with perceived olfactory qualities.…”
Section: Polymentioning
confidence: 98%
“…Second, in species where olfactory detection of odorants occurs naturally via the vapor phase, it is important to understand the role that presentation of the odorant directly in a liquid phase to a cell or tissue preparation might play in the overall characterization of their olfactory system. This is important because, as noted recently (Goyert HF et al, 2007), stimulation with liquid odorants at high (i.e., micromolar) concentrations could result in non-specific binding and, for the most reactive odorants, e.g., aldehydes and carboxylic acids , in chemical reactions with proteins that might not represent true "odorant ligand" binding.…”
Section: Vapor Concentration Range Issuesmentioning
confidence: 99%
“…In mixtures where the figure odorant was of greater concentration than the ground (8M-6L, 6M-8L), the figure odorant was identified accurately nearly every time, indicating only slight suppression of strong odors by weaker ones, while there was almost complete suppression of the weak odors by the stronger ones. Some research has demonstrated that odor mixtures create a novel perception (but not necessarily a novel quality); component qualities within the mixture are still detectable to the individual (Laing and Francis 1989) but prior adaptation to different components change which components are detectable (Goyert et al 2007). When a subject first sniffs an unfamiliar mixture of iso-intense odorants, the perception might be similar to that of seeing an ambiguous image like the Rubin image for the first time, where she may perceive a single image at first and only after repeated exposure or coaching is she able to see the alternate view.…”
Section: Discussionmentioning
confidence: 97%
“…In mixtures, adaptation would be expected to cause the odor quality to change during exposure producing successive experiences. Similarly, the ability to recognize a single component of an odor mixture depends on differences in quality of the components, and which quality a subject attends to can be manipulated by adaptation to the other components (Goyert et al 2007;Kadohisa and Wilson 2006). It is important to control and account for adaptation in experiments that study mixture suppression.…”
Section: Introductionmentioning
confidence: 98%